Prediction of Level of Job Satisfaction of Teachers on Perception of Organizational Trust of Teachers: Study of Regression Analysis - Çelebi, Nurhayat; Tatık, Ramazan Şamil (My University, 2019)
The purpose of this study is to analyze the correlation between “the level of job satisfaction” and “the perception of organizational trust” of teachers’ in terms of some variables (gender, age, branch and seniority). The relational survey method was used. The study group consists of 198 teachers working in nine high schools in Avcılar and Bakırköy districts connected to İstanbul by random sampling. In this research, “Minnesota Job Satisfaction Scale” and “Organizational Trust Scale” were used. Simple regression analysis, multiple regression analysis and correlation analysis were carried out for data analysis. According to the results of regression analysis, it was seen that the factors of internal job satisfaction and external job satisfaction were significant predictors of the organizational trust of teachers. On the other hand, the results of regression analysis of gender, age and branch variables for teachers’ job satisfaction scores were found to be insignificant. However, seniority has little effect as a predictor of job satisfaction. Furthermore, gender, age, branch and seniority variables together predicted organizational trust scores of teacher in a meaningful level. According to the results of this research, a meaningful, positive and quite high level of correlation was determined between job satisfaction and organizational trust.

Bu araştırmanın amacı, öğretmenlerin ”iş doyum düzeyleri” ile “örgütsel güven algıları” arasındaki ilişkiyi bazı değişkenler açısından (cinsiyet, yaş, branş ve kıdem) incelemektir. Araştırma, ilişkisel tarama modelinde yürütülmüştür. Araştırmanın çalışma grubu, İstanbul’a bağlı Avcılar ve Bakırköy ilçelerindeki dokuz lisede çalışan 198 öğretmenden oluşmaktadır. Bu araştırmada, “Minnesota İş Doyumu Ölçeği” ile “Örgütsel Güven Ölçeği” kullanılmıştır. Verilerin çözümlenmesinde Pearson Korelasyon Analizi, Basit Regresyon Analizi ve Çoklu Regresyon Analizi yapılmıştır.Regresyon analizi sonuçlarına göre; İçsel ve dışsal iş tatmini faktörlerinin öğretmenlerin örgütsel güvenlerinin anlamlı yordayıcıları olduğu görülmüştür. Diğer taraftan cinsiyet, yaş ve branş değişkenlerinin öğretmenlerin iş doyumu puanlarını yordamalarına ilişkin regresyon analizi sonuçları anlamsız bulunmuştur. Ancak kıdem iş doyumunun yordayıcısı olarak çok az bir etkiye sahiptir. Bunun yanında cinsiyet, yaş, branş ve kıdem değişkenleri bir arada; öğretmenlerin örgütsel güven puanlarını anlamlı düzeyde yordamaktadır. Bu araştırmanın sonuçlarına göre, iş doyumu ile örgütsel güven arasında pozitif ve oldukça yüksek düzeyde anlamlı bir ilişki saptanmıştır.
Öğretmenlerin İş Doyum Düzeylerinin Örgütsel Güven Algılarını Yordaması: Regresyon Analizi Çalışması